Introductory mathematics for engineers: Lectures in higher mathematics. Lectures in higher mathematics. - Myskis, A. D.; Volosov, V. M. (Moscow Mir Publishers, 1972)
This document is the preface to a textbook on introductory mathematics for engineers. It discusses the goals and approach of the textbook. The textbook is designed to select the most important mathematical concepts and present them in a way that helps readers apply mathematics to other fields. Proofs are simplified and intuitive explanations are prioritized over rigor. The focus is on qualitative descriptions and numerical solutions rather than formal logic. The textbook is intended to be used both in classrooms and for self-study. It covers topics in analytic geometry, linear algebra, and other applied mathematics useful for engineers and physicists.
Keywords: Mathematics- Variables and functions; mathematics- Analytic Geometry; Mathematics- Linear Algebra